Manifestations and reinforcement of heteronormativity in the workplace: A systematic scoping review - Corlett, S.; Di Marco, D.; Munduate, L.; Arenas, A. (Journal of Homosexuality, 2023)
This scoping review systematizes the evidence available to date on the manifestations of heteronormativity in the workplace. The reviewed literature shows that, at an organizational level, heteronormativity is reproduced in the configuration of space, organizational policies, and the monitoring of their accomplishment by leaders. At an interpersonal level, employees interact with others based on heterosexual presumptions, they reward what is aligned with heteronormativity, and censor what is not. Finally, individuals acting of their own volition may perform their gender in ways that strengthen the presumption of heterosexuality and communicate heteronormativity alignment. This review offers suggestions for future research in the field of heteronormativity in the workplace and includes theoretical and practical implications for the creation of inclusive organizations.